Conceptualizations of writing and the written text in the core curriculum for teaching the Polish language – a text linguistics perspective - Nocoń, Jolanta (Papers in Linguistics, 2023)
The paper attempts to reconstruct the concepts of the written text and writing competence as inscribed in the 21st-century Polish language curriculum, from the fourth grade of primary school to the matriculation exam, with reference to two linguistic approaches to text: static and dynamic. The goal of this analysis was to determine what it means to be able to write in L1 from the perspective of the authors of the analysed documents, and ultimately to reconstruct the structure of text writing competence as an expected outcome of the learning process. The conducted analysis reveals a certain tension in subsequent Polish language curricula between the conventionalization of texts written at school as products with specific characteristics, and the understanding of text as a form of verbal interaction. The model of a graduate competent at writing described in the core curricula is profiled differently each time, although a certain common basis in the form of sub-skills included in each of the analyzed curriculum documents is clearly visible. The analysis leads to a conclusion that what is fundamental to the educational process is not the choice of linguistic concepts of text as a theoretical basis for the construction of a curriculum, but the coherence of the overarching educational concept which should condition a particular model of writing skills and the written text.